1993
DOI: 10.1111/j.1432-1033.1993.tb18187.x
|View full text |Cite
|
Sign up to set email alerts
|

Photoaffinity labeling of Torpedo acetylcholine receptor by physostigmine

Abstract: The plant alkaloid physostigmine, an established anti-cholinesterase agent of the carbamate type, has recently been shown to bind to the nicotinic acetylcholine receptor from Torpedo marmorutu electrocytes [Okonjo, K. O., Kuhlmann, J. & Maelicke, A. (1991) Eur. J. Biochem. 200, Pharmacological studies of physostigmine-induced ion flux into nicotinic-acetylcholine-receptorrich membrane vesicles, indicated distinct binding sites for physostigmine and acetylcholine. As shown in this study by photoaffinity labelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 41 publications
6
51
1
Order By: Relevance
“…Allosteric potentiators, such as galantamine and physostigmine, are thought to interact with a site located in the nAChR extracellular domain (39)(40)(41), perhaps analogous to the site for potentiation of GABA A receptors by benzodiazepines (41). It appears, therefore, that nAChRs and other Cys-loop receptors can be modulated by allosteric effectors acting at multiple independent sites.…”
Section: Discussionmentioning
confidence: 99%
“…Allosteric potentiators, such as galantamine and physostigmine, are thought to interact with a site located in the nAChR extracellular domain (39)(40)(41), perhaps analogous to the site for potentiation of GABA A receptors by benzodiazepines (41). It appears, therefore, that nAChRs and other Cys-loop receptors can be modulated by allosteric effectors acting at multiple independent sites.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, physostigmine was found to activate Torpedo nAChRs as well as neuronal nAChRs expressed natively in hippocampal neurons or ectopically in fibroblasts (Okonjo et al, 1991;Pereira et al, 1993Pereira et al, , 1994. Physostigmine-induced activation of nAChRs was insensitive to blockade by competitive nAChR antagonists and could be observed when the receptors were desensitized by high agonist concentrations (Okonjo et al, 1991;Pereira et al, 1993;Schrattenholz et al, 1993). The monoclonal antibody raised against the Torpedo nAChR ␣ subunit and referred to as FK1 is the only known antagonist of the nicotinic agonistic action of physostigmine.…”
Section: Exogenous Unconventional Nachr Ligands That Modulate Receptmentioning
confidence: 99%
“…3(A); Schrattenholz et al, 1993]. Photoaffinity labeling studies carried out using [ 3 H]physostigmine and mapping of the epitope of the monoclonal antibody FK1 revealed that the region flanking the amino acid Lys-125 on the nAChR ␣ subunit contains essential elements of the physostigminebinding site and is highly conserved among different ␣ subunits and across species (Pereira et al, 1993;Schrattenholz et al, 1993;Schroder et al, 1994).…”
Section: Exogenous Unconventional Nachr Ligands That Modulate Receptmentioning
confidence: 99%
“…Materials-nAChR-rich Torpedo membrane fragments (3 mg/ml; 5 nmol of ACh sites/mg) were obtained by homogenization of Torpedo marmorata electric organ, followed by several centrifugation steps and alkaline treatment as described (11). N-␣- [propionyl-3 H]bungarotoxin (54 -68 Ci/mmol) was obtained from Amersham Pharmacia Biotech.…”
Section: Methodsmentioning
confidence: 99%
“…These studies have elucidated the overall dimensions of the receptor protein (3), its position with respect to the surrounding lipid bilayer, the locations of functional domains and amino acid residues belonging to the integral ion channel (4,5), its gating structures (6,7), and the binding sites for several classes of ligands (1,2,(7)(8)(9)(10)(11)(12). However, a high resolution three-dimensional structure of the nAChR or any other neuroreceptor is still missing.…”
mentioning
confidence: 99%